2008
DOI: 10.1002/rcs.230
|View full text |Cite
|
Sign up to set email alerts
|

Off‐pump, minimally invasive and robotic coronary revascularization yield improved outcomes over traditional on‐pump CABG

Abstract: Coronary artery disease is a global health concern, with increasing morbidity and mortality. Surgical coronary artery bypass grafting has been performed on cardiopulmonary bypass for nearly four decades, with excellent long-term durability. Beating-heart coronary surgery has been increasing in frequency in an attempt to decrease cardiopulmonary bypass-related morbidity. Furthermore, with increasing expertise and technology, minimally invasive and robotic techniques have been developed to enhance postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…Coronary bypass surgery is the most frequently performed cardiac operation worldwide and modifications are made in order to maintain more reasonable results [3]. Various improvements are recorded on surgical techniques, CPB devices, drugs and perioperative management.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary bypass surgery is the most frequently performed cardiac operation worldwide and modifications are made in order to maintain more reasonable results [3]. Various improvements are recorded on surgical techniques, CPB devices, drugs and perioperative management.…”
Section: Discussionmentioning
confidence: 99%
“…The first MIDCABs were usually performed through anterolateral thoracotomies and without CPB, also referred to as off-pump coronary artery bypass (OPCAB) [55]. OPCAB can be applied to MIDCAB or traditional full sternotomy procedures.…”
Section: Minimally Invasive Coronary Revascularizationmentioning
confidence: 99%
“…Studies comparing MIDCAB versus traditional CABG using full sternotomy have suggested such favorable results for the MIDCAB patient, including shorter hospital length of stay, earlier return to baseline physical activity and reduced transfusion requirements [6567]. Long-term graft patency using MIDCAB has been preliminarily shown to be excellent [55]. …”
Section: Minimally Invasive Coronary Revascularizationmentioning
confidence: 99%
“…In addition, with increasing expertise and technology, minimally invasive and robotic techniques have been developed to enhance post-operative recovery and patient satisfaction. 47 However, there is no study compare the effect of exercise training on conventional CABG and those new techniques, further study is needed to evaluate the difference between conventional and new surgical techniques to the outcomes in patients with CABG.…”
Section: Off-pump and Minimally Invasive Cabgmentioning
confidence: 99%